2015
DOI: 10.1007/s10865-015-9698-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding self-management behaviors in symptomatic adults with uncertain etiology using an illness perceptions framework

Abstract: The self-management behaviors of individuals with medical conditions that have an unknown etiology have not been studied. This study assesses the relationship between illness perceptions and various illness self-management behaviors in patients undergoing clinical genomic sequencing to identify a genetic cause for their condition. Hierarchical linear regression, Poisson linear regression, and logistic regression were used to assess the effect of illness perceptions (i.e., perceived consequences, timeline, pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The NCGENES 2 study seeks to build on the knowledge gained through the original NCGENES study (9,(22)(23)(24), which helped to identify which types of patients were most likely to bene t from application of exome sequencing (ES) (16,22,23,(25)(26)(27)(28)(29)(30), and examine patient decision-making to understand how they processed and responded to genomic information (31)(32)(33)(34)(35)(36)(37). Attention to enrollment of a diverse study population in the NCGENES study enabled a broad range of perspectives to be elicited, but also raised potential challenges regarding enrollment and attrition of participants from populations underrepresented in traditional research (38).…”
Section: Introductionmentioning
confidence: 99%
“…The NCGENES 2 study seeks to build on the knowledge gained through the original NCGENES study (9,(22)(23)(24), which helped to identify which types of patients were most likely to bene t from application of exome sequencing (ES) (16,22,23,(25)(26)(27)(28)(29)(30), and examine patient decision-making to understand how they processed and responded to genomic information (31)(32)(33)(34)(35)(36)(37). Attention to enrollment of a diverse study population in the NCGENES study enabled a broad range of perspectives to be elicited, but also raised potential challenges regarding enrollment and attrition of participants from populations underrepresented in traditional research (38).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the common-sense model proposes that illness perceptions are associated with the adjustments a patient makes to a health condition. Studies have shown that among individuals with medical conditions who perceive their disease as chronic, emotional impact and control over the disease due to treatment are positively associated with healthcare use, thereby enhancing the use of prescription medication and doctor recommended supplements [18]. Additionally, in patients with coronary artery disease, a better understanding of the illness enables personal control and increases quality of life [19].…”
Section: Introductionmentioning
confidence: 99%